2007
DOI: 10.1021/jp068435h
|View full text |Cite
|
Sign up to set email alerts
|

Probing Difference in Diffusivity of Chloromethanes through Water Ice in the Temperature Range of 110−150 K

Abstract: In this work, we have examined the diffusive mixing of chloromethanes in different molecular solids H 2 O, D 2 O, and CH 3 OH by monitoring their chemical sputtering spectra due to the impact of Ar + ions in the collision energy range of 3-60 eV, focusing on amorphous solid water. The chemical sputtering spectra have been monitored over the temperature window accessible by liquid nitrogen, and the coverages of the molecules of interest and ice have been varied from one to several hundred monolayers. Instrument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 42 publications
(71 reference statements)
4
46
0
Order By: Relevance
“…It is known that C 2 H 2 Cl 4 molecules cannot penetrate through ice overlayers. 25 So the intrusion of C 2 H 2 Cl 4 molecules in the neutralization process in this study can be ruled out. The thickness of C 2 H 2 -Cl 4 was varied from 10 ML to higher coverages, and it was found that the intensities were remaining the same.…”
Section: Resultsmentioning
confidence: 78%
“…It is known that C 2 H 2 Cl 4 molecules cannot penetrate through ice overlayers. 25 So the intrusion of C 2 H 2 Cl 4 molecules in the neutralization process in this study can be ruled out. The thickness of C 2 H 2 -Cl 4 was varied from 10 ML to higher coverages, and it was found that the intensities were remaining the same.…”
Section: Resultsmentioning
confidence: 78%
“…Quadrupoles are widely used mass analyzers that provide excellent ion transmission and mass resolution. At least three instruments, located at the Indian Institute of Technology (IIT) Madras (52,53), the Israel Institute of Technology (87), and the University of Arizona (88), use a quadrupole as the mass analyzer in both ion selection and analysis chambers. The instrumental designs used at IIT Madras and Arizona are very similar: Two quadrupoles are positioned at 90…”
Section: Mass Spectrometersmentioning
confidence: 99%
“…Hyperthermal energy Ar + ion scattering and sputtering are other important tools to explore the chemistry that occurs at the very top surface of molecular solids. Diffusion of small molecules such as chloromethanes and their interaction with ice have been investigated with hyperthermal energy Ar + ion sputtering (53). In this study, different chloromethane molecules were deposited on a polycrystalline copper substrate, followed by water ice deposition; the Ar + ion sputtering experiment was then performed in the temperature range between 110 and 150 K. The results showed that various chloromethane molecules diffuse at different rates through ASW.…”
Section: Molecular Diffusion/intermixingmentioning
confidence: 99%
“…These studies using LEIS are complementary to diverse analytical methods, 5,[21][22][23][24][25][26][27][28][29][30][31][32][33] which are normally used to understand molecular surfaces. All of these experimental capabilities must be built around cryogenic conditions 28,34 as well as in environments which can maintain ultralow energy ions. While efforts to create, mass select and transfer ultralow energy ions to well-defined molecular surfaces face challenges in effective ion transmission, there are also hardware restrictions to implement spectroscopies around single crystal surfaces for simultaneous experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…The surface chemistry of various molecular solids at different temperature and low pressures is interesting [34][35][36] which motivated us to design advanced instrumentation for detailed investigations. In the following, we describe ultralow energy ion scattering spectrometry coupled with reflection absorption infrared spectroscopy (RAIRS) and temperature programmed desorption (TPD), performed in the 10-1000 K window.…”
Section: Introductionmentioning
confidence: 99%